Digital repositories at the Croatian universities: providing support for the enhancement of research and teaching - Vrana, Radovan (Array, 2010)
In the last decade and a half the internet and especially the Web introduced many new types of digital information resources that have emerged and vanished demonstrating how turbulent this digital information environment can be. Today, digital technology brings together diverse materials in digital form from scattered locations on the internet in order to support work of scientists, teachers and students at universities. These user categories are constantly looking for technically advanced and enduring digital information resources which would provide them with quality (mostly peer reviewed) content. In effort to provide them with such a content, universities and academic libraries initiated development of digital repositories, digital archives of the intellectual product created by researchers, teaching staff and students. Croatian universities are part of the global information infrastructure and they already participate actively in development of different types of digital information resources including digital repositories. This paper presents results from the research in academic libraries at six Croatian universities (in Zagreb, Pula, Zadar, Rijeka, Osijek and Split) about the current state of development of digital repositories offering content for research and teaching performed at the Croatian universities.